2017
DOI: 10.1159/000452226
|View full text |Cite
|
Sign up to set email alerts
|

Enzymology and Ultrastructure of the in situ Pellicle in Caries-Active and Caries-Inactive Patients

Abstract: Aim: The present study aimed to evaluate the impact of caries activity on the key enzymes and the ultrastructure of the in situ pellicle. Methods: Pellicle formation was performed on bovine enamel slabs. Intraoral exposure (3, 30, and 120 min) was accomplished by 14 caries-active (DMFS: 22.7 ± 12.1) and 13 caries-inactive (DMFS: 1.5 ± 1.8) individuals. The enzyme activities (lysozyme, peroxidase, α-amylase, glycosyltransferase [GTF]) in the in situ pellicle and resting saliva of all participants were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
(70 reference statements)
2
4
0
Order By: Relevance
“…However, there was a tendency towards higher levels of bacterial glycosyltransferase D GTFD in subjects with open caries lesions. This finding is in accordance with the present findings with respect to differentially abundant taxa 46 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, there was a tendency towards higher levels of bacterial glycosyltransferase D GTFD in subjects with open caries lesions. This finding is in accordance with the present findings with respect to differentially abundant taxa 46 .…”
Section: Discussionsupporting
confidence: 94%
“…The present study confirms the results of a previous paper 46 where pellicle enzymes had been investigated in the same subjects. Activities of human enzymes in the pellicle layer were of high similarity in both (CC and NC) groups.…”
Section: Discussionsupporting
confidence: 92%
“…This leads to early phases of biofilm formation and by the interconnection with other species to the establishment of mature plaque (see next chapter). However, it is important to note that according to recent studies, the ultrastructure, enzyme activities, and proteomic profile of the acquired pellicle do not show major differences between otherwise healthy caries-active and inactive subjects [67,72,73].…”
Section: Bioadhesion In the Oral Cavitymentioning
confidence: 98%
“…However, because the background of the subjects cannot be aligned, the required sample size becomes large, the number of survey items is exhaustive and the research scale enormous. And it frequently happens that a sufficient scale cannot be secured, and a significant difference cannot be obtained [ 37 , 38 ]. Tautman et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the background of the subjects cannot be aligned, the required sample size becomes large, the number of survey items is exhaustive and the research scale enormous. And it frequently happens that a sufficient scale cannot be secured, and a significant difference cannot be obtained [37,38]. Tautman et al reported that there were significant differences between groups with different caries susceptibility regarding a large number of candidate proteins, but due to the small sample size, large-scale studies will be necessary in future to obtain clear differences [39].…”
Section: Discussionmentioning
confidence: 99%